Trade-off between the conflicting planning goals in correlation with patient's anatomical parameters for intensity-modulated radiotherapy of prostate cancer patients. Issue 3 (11th April 2019) - Banaei, Amin; Hashemi, Bijan; Bakhshandeh, Mohsen; Mofid, Bahram
Abstract: Aim: To quantify the relationship between the planning target volume (PTV) dose homogeneity and organs at risk (OARs) sparing in correlation with anatomical parameters in prostate intensity-modulated radiotherapy (IMRT). Materials and methods: Nine IMRT plans with various target dose constraints' priorities were created for 15 prostate cancer patients. Selected PTV and OARs parameters were calculated for the patients. A trade-off was assessed between homogeneity index (HI) and OAR sparing. Several anatomical parameters were evaluated to investigate their effects on the OAR sparing and HI. Results: Inverse exponential relationships were found between the OAR sparing and HI (average R 2 of 0·983 and 0·994 for bladder and rectum, respectively). Decreasing the priority led to more OARs sparing (normal tissue complication probability reduction: 97·6 and 74·5%; mean dose reduction: 16·3 and 11·3% for bladder and rectum, respectively) and worsening of the HI (0·095–0·322) but with no significant effect on tumour control probability. Furthermore, OARs volumes, distances between OARs and PTV and their joint volumes had stronger correlations with OARs' mean doses. Conclusion: Enforcement of target dose constraints was more effective on the improvement of HIs for the patients with initial high HI values at low dose constraints' priorities. Reducing the priority had more effects on the OARs sparing compared to HI, especially for the patients with high OAR doses in high priority plans. This can be attributed to smaller distances or greater joint volumes between the OARs and PTV.